Religion and culture: forms and peculiarities of relationship - Шавріна, I. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
This article analyzes the main characteristics of the functioning of culture and religion on the verge of XIX - XX and XX-XXI centuries. These processes are compared with the modern features of culture and religion in the Ukrainian society. The methodological basis is the views of V. Asmus, P. Sorokin, E. Toffler, H. Aliayev and others. The above-mentioned periods are considered as a transitional era in the historical movement not only of a certain society, but of all mankind, that turns the culture and religion towards the particular orientation to destruction, negative as it is. Particular attention is paid to the views of V. Soloviov and N. Berdyaev.